2021
DOI: 10.1007/s43678-020-00069-5
|View full text |Cite
|
Sign up to set email alerts
|

Infographics, podcasts, and blogs: a multi-channel, asynchronous, digital faculty experience to improve clinical teaching (MAX FacDev)

Abstract: Attendance at faculty development events are often limited to those with time and interest, but all clinical teachers should have access to continuing faculty development. A multi-channel, asynchronous, digital faculty experience strategy (MAX FacDev) was used to engage busy emergency medicine (EM) teachers associated with a distributed medical education network involving ten geographically distinct teaching sites. An evidence-informed education bundle on key principles for clinical teaching was developed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…This study confirmed that infographics are adaptable to an array of clinical specialties and can be successfully implemented as a technology-enhanced pedagogical tool (Thoma et al, 2018;Chin et al, 2019;Dowhos et al,2021) providing residents with the capacity to apply teaching skills 'just in time' in the clinical setting. A positive outcome was faculty satisfaction with the JiTT program and their ability to role model teaching skills, which leads to a positive aura of the JiTT program in the clinical environment.…”
Section: Discussionsupporting
confidence: 69%
“…This study confirmed that infographics are adaptable to an array of clinical specialties and can be successfully implemented as a technology-enhanced pedagogical tool (Thoma et al, 2018;Chin et al, 2019;Dowhos et al,2021) providing residents with the capacity to apply teaching skills 'just in time' in the clinical setting. A positive outcome was faculty satisfaction with the JiTT program and their ability to role model teaching skills, which leads to a positive aura of the JiTT program in the clinical environment.…”
Section: Discussionsupporting
confidence: 69%
“…Nevertheless, it also became obvious that medical education without borders demanded accessible evidence-based content and professional, factual discussion forums beyond institutional LMS boundaries or central resources. Learners needed new ways to flourish in a world where individuals and institutions are progressively more interconnected and interdependent (Dowhos et al, 2021). However, additional challenges rooted deeply in human nature as well as the tenets of active learning soon became evident.…”
Section: The Role Of Blogs In Medical Educationmentioning
confidence: 99%
“…The lack of important social connection elements (e.g., rapport), the absence of learner-centered education (e.g., activating prior knowledge), and the need for the invigoration of post-session discussion all impeded the establishment of cooperative learning communities. The formation of such communities was hampered further by the lack of access to evidence-based, asynchronous education as needed to accommodate learners across the continuum of healthcare professions education, independent from their geographic location, time zone, or schedule (Dowhos et al, 2021).…”
Section: The Role Of Blogs In Medical Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the challenges faced by the previous studies that have been presented above, both from nondigital free media and the pandemic itself, this is the basis for researchers to shift to digital-based media with good intentions in terms of effectiveness and efficiency and as a solution to the impact of the Covid-19 pandemic itself (Chongpornchai et al, 2021;Dowhos et al, 2021). Moreover, the results of infographic media and videos from students' guidance and counseling can be used as a solution for the provision of limited face-to-face services.…”
Section: Introductionmentioning
confidence: 99%